The Impact of Turkish Foreign Policy Transformations on Libya"economic Interests and Geopolitical Strategies: Türkiye'srole in the Libyan Conflict" (2011-2023) - ALWARFALLİ, MUTASEMBELLAH (İstanbul Kültür Üniversitesi, 2025)
This thesis investigates the intricate dynamics of Libyan-Turkish relations from 2011 to 2023, focusing on Turkey's emergence as a key external actor amidst significant regional geopolitical changes. As Libya underwent profound internal turmoil, Turkey adapted its foreign policy to address the shifting conflict landscape and political instability. The research delineates four critical phases of engagement: the early Libyan revolution (2011-2013), the period of political division and Turkey's ensuing stance (2014-2018), Turkey's military intervention in support of the Government of National Accord (GNA) (2019-2021), and the implications of this involvement on regional stability (2021-2023). By analyzing these phases, the study reveals the motivations driving Turkish policy shifts, including strategic interests, regional security concerns, and the quest for influence in the Eastern Mediterranean. It assesses Turkey's challenges navigating the complex Libyan landscape and its broader implications for sovereignty and regional dynamics. Ultimately, the findings highlight that Turkey's engagement has been shaped by a confluence of geopolitical ambitions and local realities, impacting the trajectory of relations between the two nations. This study employs a multifaceted methodology to examine the evolution of Turkish foreign affairs, focusing on two distinct national contexts: Turkey and Libya. Since these are bilateral relations between two countries, the national level of analysis was used; however, at some stages, the international analysis was called for and used due to the intervention of new players influencing the relations between the two countries. Utilizing descriptive analysis and a case study approach, the research explores the dynamics of Turkish foreign policy transformations through a structured time frame system within the narrative. Additionally, the study incorporates theoretical frameworks such as defensive realism and social constructivism to provide a nuanced understanding of the factors influencing these changes. Through this analysis, the thesis offers a nuanced understanding of Turkey's evolving role in Libya and its significance in broader regional developments.
Keywords: Geopolitical Dynamics /Eastern Mediterranean issue / Libya and Turkey Bilateral Relations / Descriptive Analysis / Foreign Policy Change /Balance of Power